2015
DOI: 10.1007/s11481-015-9630-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Stage-Specific Inflammatory microRNA Profiling in Urine During Disease Progression in Experimental Autoimmune Encephalomyelitis: Markers of Disease Progression and Drug Response

Abstract: Recently, microRNAs (miRNAs) have been implicated in regulating neuroinflammatory and demyelinative responses in multiple sclerosis (MS) and its mouse model of experimental autoimmune encephalomyelitis (EAE). miRNAs have also been studied as biomarkers of disease pathology and drug-response in MS. However, no complete miRNA profiling at various stages of EAE disease has been examined, especially in the urine. We carried out a systematic analysis of miRNAs in the urine exosomes as well as in the plasma and spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…8 0 . 0041 1.1 0.9369 downregulated in both MS active and inactive lesions versus normal brain WM 17 ; upregulated in MS CD4+ T cells versus HC 41 ; upregulated in plasma of EAE mice vs control 36 miR-142a-5p −1.1 0.8945 2 . 5 0 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 0 . 0041 1.1 0.9369 downregulated in both MS active and inactive lesions versus normal brain WM 17 ; upregulated in MS CD4+ T cells versus HC 41 ; upregulated in plasma of EAE mice vs control 36 miR-142a-5p −1.1 0.8945 2 . 5 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Next, we asked if the miRNAs identified by miR-Seq and validated in the neurons of EAE mice were previously described as differentially regulated in other tissues and cells in EAE and/or MS. Of the 27 regulated miRNAs in motor neurons, 13 have been previously implicated in EAE and/or MS (Table 1 ). Regulation of individual miRNAs was previously identified in immune populations including lymph nodes 29 , whole blood 30 , 31 , serum 32 35 , plasma 36 , peripheral blood mononuclear cells (PBMCs) 35 , 37 , leukocytes 38 , 39 , CD3+ T cells 40 , CD4+ T cells 41 , 42 , T regulatory cells (T regs ) 20 , or B cells 43 ; or in the brain within MS lesions 17 , 44 or normal appearing white matter (NAWM) 21 , 45 , 46 . In a small number of cases the miRNA of interest was genetically manipulated for investigation in EAE 47 50 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in the animal model of MS (experimental autoimmune encephalomyelitis, EAE), genetic deletion of the miRNA cluster miR-106a∼363 (containing Natalizumab-regulated miR-20b) resulted in a more severe disease course, and it upregulated in vivo the miR-20b target genes [89]. In addition, the treatment with Natalizumab restored the expression levels of miR-26a and miR-155 [90], which were upregulated in PBMCs of MS patients, as well as in urine exosome, plasma, and in the spinal cord samples from EAE mice [82]. Notably, miR-155 plays a central role in many processes involved in the pathogenesis of MS, such as immune cell activation, neurodegeneration and permeabilization of the BBB [18].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…The pioneer study on the miRNA modulation by GA reported that the administration of GA was able to restore normal levels of miR-146a and miR-142-3p, which were upregulated in PBMCs of the RRMS patients [81]. Later, Singh et al [82] demonstrated that GA treatment was able to modulate the expression levels of miR-155-5p, miR-27a-3p, miR-9-5p, and miR-350-5p, in plasma and urine exosome, so they were suggested as potential biomarkers of drug response. Glatiramer Acetate, Interferon-β, and Dimethyl fumarate, are shown in green, blue, purple, orange, and brown, respectively.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Recently, significant advances have been made in the search for biomarkers in MS. In EAE, differential miRNA profiles for each phase of disease (pre‐onset, onset, disease peak) may provide valuable insight into putative biomarkers for MS diagnosis (Singh et al, ). Several miRNAs identified were also differentially regulated with glatiramer acetate treated individuals, suggesting that changes in EV‐derived miRNAs may present a useful and non‐invasive method to monitor treatment efficacy.…”
Section: Extracellular Vesicle Localized Mirnas As Biomarkers For Cnsmentioning
confidence: 99%